PHYSICOCHEMICAL, FUNCTIONAL AND SENSORY PROPERTIES OF PROTEIN EXTRACTED FROM DESICCATED COCONUT - F. Rasyid; P. M. T. Hansen (International Coconut Community, 1993)
Coconut protein (CNP) was extracted from desiccated coconut in 1.0 M sodium chloride (1:15), precipitated by HCI, ultra filtered, and freeze‑dried. The physicochemical, functional, and sensory characteristics of the material were compared with those of soy protein. The composition and chemical analyses included measurements of protein, fat, moisture, carbohydrate, ash, minerals, and amino acids. Other measurements included determination of die contents of sulfhydryl and disulfide groups, hydrophobicity values, and electrophoretic patterns of CNP and soy protein. The bulk density of the protein preparations was also measured. Chemical analyses showed that CNP was comparable in overall composition to the reference soy protein with the exception of high sodium content (4.7%). Amino acid analysis revealed a higher content of arginine and a lower content of aspartic acid and lysine. A test for relatedness among, proteins (S ΔQ) showed very little similarity between the amino acid profiles of the two protein entities. CNP was found to be more hydrophobic than soy protein and contained slightly less sulthydryl and disulfide groups. The disparity in the above values was reflected in dissimilarity in the electrophoretic patterns between CNP and soy protein. CNP exhibited a lower solubility but possessed a similar water binding and a higher lipid absorption capacity than soy protein. Sensory evaluation using crackers prepared with different amounts of the two proteins showed that crackers with added CNP were preferred over crackers with added soy protein. The overall results of this study suggest a potential use of CNP as an alternative protein source to soy protein for use in manufactured foods where solubility is not a critical factor.